2008
DOI: 10.1037/a0012704
|View full text |Cite
|
Sign up to set email alerts
|

Getting even for customer mistreatment: The role of moral identity in the relationship between customer interpersonal injustice and employee sabotage.

Abstract: Research on the "dark side" of organizational behavior has determined that employee sabotage is most often a reaction by disgruntled employees to perceived mistreatment. To date, however, most studies on employee retaliation have focused on intra-organizational sources of (in)justice. Results from this field study of customer service representatives (N = 358) showed that interpersonal injustice from customers relates positively to customer-directed sabotage over and above intra-organizational sources of fairne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
472
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(497 citation statements)
references
References 68 publications
(79 reference statements)
12
472
1
4
Order By: Relevance
“…These "locked in" employees while maintaining organizational membership might actively engage in behaviors that are unfavorable and counter to the organization's interest (Crino, 1994;Terris & Jones, 1982). Empirical results support this argument, it has been shown that sabotage and stealing are adaptive behaviors adopted by employees in response to unfavorable incidents (Greenberge, 1990;Skarlicki, Van Jaarsveld & Walker, 2008).…”
Section: Workplace Bullying-unethical Behaviorssupporting
confidence: 56%
“…These "locked in" employees while maintaining organizational membership might actively engage in behaviors that are unfavorable and counter to the organization's interest (Crino, 1994;Terris & Jones, 1982). Empirical results support this argument, it has been shown that sabotage and stealing are adaptive behaviors adopted by employees in response to unfavorable incidents (Greenberge, 1990;Skarlicki, Van Jaarsveld & Walker, 2008).…”
Section: Workplace Bullying-unethical Behaviorssupporting
confidence: 56%
“…A myriad of other factors has been proposed to explain CWB, which could stem from abusive supervisors and customers toward employees to violation of psychological contract (e.g., termination of one's employment on grounds of perceived supervisor vendetta rather than one's poor job performance), work events, and unfavorable working conditions [10][11][12][13]. Deviant work behavior can result from employees who feel mistreated by others in the organization and could be a way to retaliate against other employees.…”
Section: Explanation Of Counterproductive Work Behavior (Cwb)mentioning
confidence: 99%
“…Research that investigates precisely when moral identity may influence behavior remains relatively sparse. Thus far, scholars have looked at the interaction between moral identity and formalism (Reynolds & Ceranic, 2007), at the interaction between moral identity and ethical organization culture (Skarlicki, van Jaarsveld, & Walker, 2008), and at the interaction between internal and symbolic moral identity (Caldwell & Moberg, 2007). We add to this existing literature and illuminate how moral identity operates.…”
Section: Theoretical Implicationsmentioning
confidence: 99%